Regulasi Emosi Ditinjau Dari Dukungan Sosial Teman Sebaya Pada Siswa SMP - Cessna Nada Salsabila; Yulia Fitriani (UPT Publikasi dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2023)
Relationship between Emotion Regulation and Peer Social Support (Correlational Study of Emotion Regulation in View of Peer Social Support in Students in Junior High School X). The aim of this study to determine the relationship between emotional regulation and peer social support in students at X Junior High School. This study used a quantitative method with a correlational study. The subjects in this study were students of X Junior High School, using data collection techniquesCluster Random Sampling. The sample in this study amounted to 150 students. The measuring instrument used is a Likert scale. Based on the results of correlation analysisSpearman’s rho, it is known that there is a positive relationship between Emotion Regulation and Peer Social Support in students with a significance value of 0.000 (p<0.05) which means (Ha) is accepted and (Ho) is rejected, which means there is a positive relationship between Emotion Regulation and Social Support Friends of the same age. The relationship between Emotion Regulation and Peer Social Support has a correlation value of 0.320. these results indicate that, the higher the Peer Social Support, the higher the Emotion Regulation in Junior High School X students.________________________________________________________Hubungan antara Regulasi Emosi dengan Dukungan Sosial teman Sebaya (Studi Korelasional tentang Regulasi Emosi diTinjau dari Dukungan Sosial Teman Sebaya Pada Siswa di Sekolah Menengah Pertama X). Penelitian ini bertujuan untuk mengetahui hubungan antara regulasi emosi dengan dukungan sosial teman sebaya pada siswa di Sekolah Menengah Pertama X. Penelitian ini menggunakan metode kuantitatif dengan studi korelasional. Subjek dalam penelitian ini adalah siswa Sekolah Menengah Pertama X, dengan teknik pengambilan data Cluster Random Sampling. Sampel dalam penelitian ini berjumlah 150 orang siswa. Alat ukur yang digunakan ialah skala likert. Berdasarkan hasil analisis korelasi Spearman’s rho, diketahui bahwa terdapat hubungan yang positif antara Regulasi Emosi dengan Dukungan Sosial teman Sebaya pada siswa dengan nilai signifikansi 0.000 ( p < 0.05) yang artinya (Ha) diterima dan (Ho) ditolak, yang berarti terdapat hubungan yang positif antara Regulasi Emosi dengan Dukungan Sosial Teman Sebaya. Hubungan antara Regulasi Emosi dengan Dukungan Sosial Teman Sebaya memiliki nilai korelasi sebesar 0.320. hasil tersebut menunjukkan bahwa, semakin tinggi Dukungan Sosial Teman Sebaya maka semakin tinggi pula Regulasi Emosi pada siswa Sekolah Menengah Pertama X.